A Cross-Canada Study of High School Art Teachers - Gray, James; MacGregor, Ronald (Canadian Journal of Education/Revue canadienne de l'éducation, 1991)
In A Place Called School (1984) Goodlad suggested that art teaching in American schools was characterized by make-work projects, lack of concern for individuality, and general fuzziness of goals. To determine whether the same could be said of art teaching in Canada, we studied 59 high schools across the country. We conclude that Canadian art teachers enjoy considerable autonomy in what they teach and how they teach it. Teachers' goals for the students, while often developed from personal experience rather than from identifiable prescriptive sources, nevertheless have sufficient commonality that their subject can be characterized as ``art.' Our study's profile of the Canadian high school art teacher is more complex than that in Goodlad's American research. Dans A Place Called School (1984), Goodlad avance que les cours d'arts plastiques dans les écoles américaines sont au fond des cours de remplissage dont les objectifs sont en général assez flous. Pour déterminer s'il en est de même au Canada, nous avons étudié 59 écoles secondaires d'un océan à l'autre. Nous sommes maintenant en mesure de conclure que les enseignants en arts plastiques jouissent d'une très grande autonomie quant à la matière enseignée et aux méthodes pédagogiques. Si les buts que fixent les enseignants à leurs élèves sont souvent dérivés de l'expérience personnelle plutôt que de sources normatives identifiables, ils sont suffisamment semblables pour que la matière à laquelle ils se rattachent soit identifiée sous la dénomination ``arts plastiques.' Le profil que trace notre étude de l'enseignant en arts plastiques au secondaire est plus complexe que celui qui ressort de la recherche menée par Goodlad aux États-Unis.